2018
DOI: 10.1103/physrevd.98.034004
|View full text |Cite
|
Sign up to set email alerts
|

Possible interpretation of the newly observed Ω(2012) state

Abstract: Inspired by the newly observed Ωð2012Þ state at Belle II, we investigate the two-body strong decays of Ω baryons up to N ¼ 2 shell within the chiral quark model. Our results indicate that (i) the newly observed Ωð2012Þ state could be assigned to the spin-parity J P ¼ 3=2 − state j70; 2 10; 1; 1; 3 2 − i and the experimental data can be reasonably described. However, the spin-parity J P ¼ 1=2 − state j70; 2 10; 1; 1; 1 2 − i and spin-parity J P ¼ 3=2 þ state j56; 4 10; 2; 0; 3 2 þ i cannot be completely exclude… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
70
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(93 citation statements)
references
References 45 publications
19
70
4
Order By: Relevance
“…Moreover, the possibility of the broad structure arising from the overlapping of Ξ ′ c |1P λ 1/2 − 1 and Ξ ′ c |1P λ 1/2 − 2 cannot be ruled out as well. Finally it should be mentioned that combining our previous study [49] of the newly observed Ω * b states at LHCb [50], we find that the Ξ c (2923) 0 , Ξ c (2939) 0 , and Ξ c (2965) 0 may be flavour partners of Ω b (6330), Ω b (6340), and Ω b (6350), respectively. The missing mixed state Ξ ′ c |1P λ 1/2 − 1 may be a flavour partner of Ω b (6316).…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, the possibility of the broad structure arising from the overlapping of Ξ ′ c |1P λ 1/2 − 1 and Ξ ′ c |1P λ 1/2 − 2 cannot be ruled out as well. Finally it should be mentioned that combining our previous study [49] of the newly observed Ω * b states at LHCb [50], we find that the Ξ c (2923) 0 , Ξ c (2939) 0 , and Ξ c (2965) 0 may be flavour partners of Ω b (6330), Ω b (6340), and Ω b (6350), respectively. The missing mixed state Ξ ′ c |1P λ 1/2 − 1 may be a flavour partner of Ω b (6316).…”
Section: Discussionsupporting
confidence: 70%
“…To identify the properties of the Ωð2012Þ baryon, it would also be helpful to investigate its other properties besides the mass. Its strong decay was studied recently in [15], using the chiral quark model, and as a result, the possibility of Ωð2012Þ being J P ¼ 3=2 − was underlined; however, it also stated that the results obtained for the possibility of it being J P ¼ 1=2 − or J P ¼ 3=2 þ are consistent with the results of the Belle Collaboration within the uncertainties. There are also some studies on the radiative decays [16] and magnetic moments of negative parity baryons [17,18].…”
supporting
confidence: 73%
“…They are determined by fitting the masses of four Ω resonances: (i) The ground state Ω(1672) [2], which is well established in experiments. (ii) The newly observed Ω(2012) resonance at Belle [15], which is interpreted as the first orbital excited state Ω(1 2 P 3/2 − ) [16,17]. (iii) The other first orbital excited state Ω(1 2 P 1/2 − ) whose mass is predicted to be ∼ 1950 MeV within the Lattice QCD [13] and the relativized quark models [5,6].…”
Section: Resultsmentioning
confidence: 96%
“…The Ω(2250) resonance listed in RPP [2] which is assigned as the Ω(1 4 D 5/2 + ) state according to our previous studies [16]. The determined parameter set is listed in Table IV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation